Аукцион: [роман] / Юлиан Семенов - Семенов Юлиан Семенович (Военные приключения, 2008)
Экземпляры: ф.10 (20230302) / Инвентарный номер: 63239 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 30 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44